(untitled) (Journal of Economic Research & Business Administration, 2015)
Currently, performance audit is one of the main types of financial control. Performance audit is aimed at testing how effectively and economically spent public funds. Such control includes not only specific aspects of management , but also the entire management activities, including organizational and administrative systems . In this regard, in this article the basic rules and procedures to be followed in the process of planning, conducting and recording the results of audit efficiency. They determine the order in which those objects and efficiency audits , their preliminary examination preparation program checks the formulation of its objectives and issues, as well as the development of performance criteria ; considering methods of conducting audits , prepare findings , conclusions and recommendations based on their results ; set out the requirements for the structure and design of the report on the audit